Can platelet Iymphocyte ratio and neutrophil to lymphocyte ratio be used as prognostic predictors for hepatocellular carcinoma? (Annals of Medical Research, 2021)
None
Keywords: Hepatocellular Carcinoma; Platelet To Lymphocyte Ratio; Neutrophil To Lymphocyte Ratio; Treatment Response; Recurrence.